EKSPLORASI ETNOMATEMATIKA MODEL IKAT TERNAK MASYARAKAT DAWAN DALAM PEMBELAJARAN MATEMATIKA PADA MATERI LINGKARAN - Penina M Kikhau; Dian S Nenoliu (MEGA: Jurnal Pendidikan Matematika, 2020)
Mathematics is a field of science whose application is often found in everyday life. In studying mathematics, there are two scopes taught, namely mathematics which is taught in education and ethnomatematics which is the application of mathematics in cultural groups. The application of local culture in learning activities can make it easier for students to learn because what is learned is directly related to students' daily lives. The people of East Nusa Tenggara generally develop several livestock raising systems, one of which is a semi-intensive system, in which livestock are kept outside of cages and tied under lush trees. This culture of binding livestock can be found in almost all Dawan people who live in the suburbs to outside the city. The culture of the beef tie in the Dawan community can be applied in an academic environment as an approach to learning mathematics on circular material. This study aims to explore the ethnomatematics of the Dawan culture of the cow tie. This research uses ethnographic method. The data in this study were obtained using triangulation of data obtained through field observations, oral interviews and documentation. The exploration results show that the cattle tie model can be used in studying circles such as the elements of a circle, the area of ​​a circle, the circumference of the circle and the area of ​​a circle.